Shakespeare. Stwarzanie świata Stephena Greenblatta, czyli odkrywczość kulturowej mozaiki - Krystek, Jędrzej (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article is an attempt to analyze the narrative and methodological techniques of new historicism. The basis for the analysis was Stephan Greenblatt’s book Will In the Word. How Shakespeare Became Shakespeare, especially because of of creating biographical and intercultural areas. The author of the analysis follows the relations between the truth of narration and historical truth and tries to determine the constituent elements of Hamlet’s author. The author of the analysis traced the relations between two truths: the truth of the historical time and the truth of the narrative time.